BEYOND JUDICIAL INTERVENTION: COLLABORATIVE LAW AS A NOVEL APPROACH TO CONFLICT RESOLUTION - Dorczak, Anita (European Scientific Journal, ESJ, 2015)
This paper analyzes the main characteristics of the collaborative approach to conflict resolution. It traces its history and development across the continents. The comments of the participants from the research conducted by the International Academy of Collaborative Practitioners (IACP) are reviewed and the success rate is presented. The author posits that collaborative law, a non-adversarial approach to resolving conflict, has been successful in the area of family disputes and should be used worldwide in other types of disputes allowing the court systems to only manage the truly adversarial cases with the litigants disinterested in win-win solutions.